2008
DOI: 10.1016/j.aquaculture.2008.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenetic cycle and reproductive effort assessed by two methods in 3 age classes of Pacific oysters, Crassostrea gigas, reared in Normandy

Abstract: Two methods were used to estimate the reproductive output of female Pacific oysters reared in Normandy: histology with image analysis and ELISA (Enzyme-Linked ImmunoSorbent Assay) which allowed the quantification of egg protein. Condition indices, gonad area and gametogenetic stages of the oysters were determined in the entire population (males and females) between May and October 2005. All investigations were performed in 3 age classes: oysters in their first, second or third years (corresponding to spat, hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 27 publications
3
46
0
1
Order By: Relevance
“…Relationships between food quality and quantity, energy storage, and reproduction are now well established in C. gigas (Soudant et al, 1999;Berthelin et al, 2000;Royer et al, 2008;Rico-Villa et al, 2009). These observations suggest that HAB exposure, by affecting nutrition-related functions, may impact reproduction processes and gamete output.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between food quality and quantity, energy storage, and reproduction are now well established in C. gigas (Soudant et al, 1999;Berthelin et al, 2000;Royer et al, 2008;Rico-Villa et al, 2009). These observations suggest that HAB exposure, by affecting nutrition-related functions, may impact reproduction processes and gamete output.…”
Section: Introductionmentioning
confidence: 99%
“…En el trabajo de Pazos, Román, Acosta, Abad & Sánchez (1996) se evaluó el efecto de la talla Mytilus edulis sobre sus estadios gonádicos, reportando que los individuos juveniles mostraron un solo periodo de liberación anual, mientras que los adultos liberaron en dos ocasiones. En contraste, Royer et al (2008) al estudiar el desarrollo de la madurez gonadal en tres clases de tallas para Crassostrea gigas, reportaron que su ciclo reproductivo no presentó diferencia en función de la talla del ostión. En este mismo sentido, Quayle (1969) sugiere que el inicio en la actividad reproductiva en Crassostrea gigas, está más relacionado con factores ambientales (temperatura, salinidad, pluviometría, corrientes y alimento disponible) que con la misma talla del ostión.…”
Section: Discussionunclassified
“…On examining the median part of the visceral mass, Royer et al (2008) found the percentage surface occupied by the gonad to be directly linked to the number and/or size of gametes produced and therefore representative of reproductive effort, which is linked to the proportion of energy allocated to reproduction (Todd and Havenhand, 1983;Normand et al, 2009). In the DEB theory, oyster reproductive effort was found to depend mostly on the halfsaturation coefficient for ingestion (Bernard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For each sample, a 3 mm crosssection of the visceral mass was excised in front of the pericardic region and immediately fixed in modified Davidson's solution at 4°C for 48 h. In order to avoid any bias related to the cut of the median section through the visceral mass, these cuts were always made at the same position by the same person and the same manner (Royer et al, 2008). Sections were dehydrated in ascending ethanol solutions, cleared with the xylene substitute Microclearing (Diapath, Italy), and embedded in paraffin wax.…”
Section: Histologymentioning
confidence: 99%